Coptis chinensis Franch polysaccharides provide a dynamically regulation on intestinal microenvironment, based on the intestinal flora and mucosal immunity. (1st March 2021) - Chen, Qingqing; Ren, Rongrong; Zhang, Qingqing; Wu, Jingjing; Zhang, Yufeng; Xue, Mingsong; Yin, Dengke; Yang, Ye
Abstract: Ethnopharmacological relevance: Coptis chinensis Franch is one of the most widely used traditional Chinese herbs in China and was firstly recorded in "Shennong's Classic of Materia Medica" in the Han Dynasty. The medical records in past thousands years have fully confirmed the clinical efficacies of Coptis chinensis Franch against intestinal diseases. The polysaccharides in herbal medicines can be digested by the flora and uptaken by the Peyer's patches (PPs) in intestine. It can be reasonably presumed that the polysaccharides in Coptis chinensis Franch (CCP) should be one of the critical element in the regulation of intestinal microenvironment. Aim of the study: This study intended to explore the dynamic regulation of CCP on intestinal microenvironment from the perspective of the intestinal mucosal immunity and the intestinal flora, in order to provide a new research perspective for the pharmacological mechanism of Coptis chinensis Franch. Materials and methods: The absorption and distribution of CCP in intestinal tissues were observed after the perfusion of FITC labeled CCP. The influences of CCP on intestinal flora were evaluated by the 16sRNA gene illumina-miseq sequencing after gavage. The regulations of CCP on intestinal mucosal immunity were evaluated by the immunohistochemical analysis of the interferon-γ (IFN-γ), interleukin-4 (IL-4), interleukin-17 (IL-17) and transforming growth factor-β (TGF-β) secretion in PPs and intestinal epithelial tissue. Results: With the self-aggregation into particles morphology, CCP can be up-taken by PPs and promote the IFN-γ, IL-4, IL-17 and TGF-β secretion in PPs in a dose-dependent manner. The CCP can also be utilized by the intestinal flora and dynamically regulate the diversity, composition and distribution of the intestinal flora. The temporal regulations of CCP on IFN-γ, IL-4, IL-17 and TGF-β secretions in intestinal epithelial tissues are consistent with the variation tendency of intestinal flora. Conclusion: CCP can provide effective, dynamical and dose-dependent regulations on intestinal microenvironment, not only the intestinal flora but also the PPs and intestinal epithelium related immune response. These may be involved in the multiple biological activities of Coptis chinensis Franch. Graphical abstract: Image 1 Highlights: Coptis chinensis Franch Polysaccharides (CCP) enters PPs in the form of particle. CCP can dynamically regulate intestinal flora diversity；. CCP can dynamically regulate the intestinal immune microenvironment.